Stereo type dan Labelling Terhadap Perempuan Pada Berita “19 Detik Gisella Anastasia” di Portal Okezone.com dan Kompas.com - Tiara Angelica; Reni Nuraeni (Jurnal Visi Komunikasi, 2022)
In November 2020, public attention was drawn to the immoral video issue involving the artist Gisella Anastasia. The case is synonymous with the term "19 Seconds," as the duration of the footage that has been distributed publicly is 19 Seconds. As a result, the media, notably okezone.com and kompas.com, turned their attention to this matter. The purpose of this study is to examine how the media outlets okezone.com and kompas.com covered the 19 Seconds immoral video case and framed the female figure in the 19 Seconds of Gisella Anastasia immoral video case in order to foster stereotypes and stigma against women. Pan and Kosicki framing analysis is used in this study to determine how the media outlets okezone.com and kompas.com construct immoral video reporting through the text and images that appear on the immoral video news 19 Seconds Gisella Anastasia. The study's findings indicate that the news portals okezone.com and kompas.com frequently discuss Gisella Anastasia